PEMBINAAN KARAKTER ENTREPRENEUR PADA SISWA SMK PERMATA HARAPAN 2 BATAM - Purba, Tiurniari; Vargo Christian L. Tobing; Erni Yanti Natalia; Nora Pitri Nainggolan; Mortigor Afrizal Purba (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Entrepreneurs are individuals who run businesses or entrepreneurship with the aim of seeking profit or identifying business opportunities and taking the initiative to innovate. The easiest individuals to teach are school children, children who are undergoing formal education at school. It will be much easier to recognize and introduce entrepreneurial characters to school children because they spend their days at school. This PKM activity will combine lecture, discussion and training methods carried out at SMK Permata Harapan 2 Batam and attended by 30 participants. The results of the coaching showed that the obstacles that made the coaching participants never think of becoming an entrepreneur were not having a clear vision, not daring to take risks, having difficulty focusing on goals, not being used to having problem solving skills, and lacking an innovative spirit. After coaching, it was found that the participants had high self-confidence in their abilities and ideas, were open to change, had an innovative and creative spirit to create products, and were able to analyze problems, find solutions.